2022
DOI: 10.1111/jfbc.14111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protective effects of morin against acrylamide‐induced lung toxicity by biomarkers of oxidative stress, inflammation, apoptosis, and autophagy

Abstract: From past to present, various plants (especially medicinal and aromatic plants) or their products have been used for therapeutic purposes for the treatment of various diseases that humanity suffers from,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…It has also been shown that Morin ameliorates oxidative stress by modulating antioxidant enzymes in various models, including testicular toxicity in rats. [50,[52][53][54][55] Our results also showed decreased expression and localization of GCNA, which is a marker of germ cell proliferation; moreover, Morin treatment increased GCNA expression in mouse testis. This finding suggests that Morin can stimulate germ cell F I G U R E 4 Effects of in vivo administration of Morin on the circulating testosterone levels and on the expression of germ cell nuclear acidic protein (GCNA) and visfatin.…”
Section: Effect Of Morin On the Immunolocalization Of Gcna Visfatin A...supporting
confidence: 60%
See 1 more Smart Citation
“…It has also been shown that Morin ameliorates oxidative stress by modulating antioxidant enzymes in various models, including testicular toxicity in rats. [50,[52][53][54][55] Our results also showed decreased expression and localization of GCNA, which is a marker of germ cell proliferation; moreover, Morin treatment increased GCNA expression in mouse testis. This finding suggests that Morin can stimulate germ cell F I G U R E 4 Effects of in vivo administration of Morin on the circulating testosterone levels and on the expression of germ cell nuclear acidic protein (GCNA) and visfatin.…”
Section: Effect Of Morin On the Immunolocalization Of Gcna Visfatin A...supporting
confidence: 60%
“…It has also been shown that Morin ameliorates oxidative stress by modulating antioxidant enzymes in various models, including testicular toxicity in rats. [ 50,52–55 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is also found that the mRNA expression levels of proapoptotic Bax and procaspase-3 signifcantly were higher after AA exposure, and the levels of antiapoptotic Bcl-2 were relatively lower. Moreover, the ratio of either p-ERK/ERK or p-JNK/JNK was signifcantly elevated by AA [94].…”
Section: Acrylamide Induces Apoptosis In Liver Kidney and Lungmentioning
confidence: 94%
“…It was shown that AAinduced-infammatory responses could cause pulmonary dysfunction and increase systemic infammation. Specifcally, AA resulted in signifcantly elevated levels of NF-κB, IL-1β, TNF-α, and COX-2 in lung tissue [94]. Tese evidence suggested that pyroptosis represents as one of the crucial mechanisms of AA toxicity.…”
Section: Acrylamide Induces Pyroptosis In Liver Kidney and Lungmentioning
confidence: 99%